2017
DOI: 10.1002/jmri.25927
|View full text |Cite
|
Sign up to set email alerts
|

Lateral ventricular volume measurement by 3D MR hydrography in fetal ventriculomegaly and normal lateral ventricles

Abstract: 1 Technical Efficacy Stage 1 J. Magn. Reson. Imaging 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…With the same capabilities as MSP, 3D MRH requires less time (4 min VS12 min) and contains excellent inter-rater agreement and intra-rater repeatability. [14]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the same capabilities as MSP, 3D MRH requires less time (4 min VS12 min) and contains excellent inter-rater agreement and intra-rater repeatability. [14]…”
Section: Discussionmentioning
confidence: 99%
“…[24] The differences may be attributable to race, heterogeneous cohorts, and different methodology. In our previous study, the volume obtained using 3D MRH was shown to be slightly greater than that obtained using MSP [14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the pixel and spacing information, volume models enable the observation of structures in a body not only on classical horizontal, coronal, and sagittal planes for the diagnosis of common diseases,1 but also on various oblique planes for specific clinical fields, such as a probe's eye and trajectory view on the magnetic resonance images (MRIs) in deep brain stimulation surgery,23 neuro-ocular plane on computed tomographs (CTs) of ophthalmology,45 and ultrasonographic view for heart and liver diagnoses 67. Furthermore, volume models of MRIs can be used for volumetric analysis of a structure for the diagnosis of various diseases89 and for human simulation purposes, such as phantoms for electromagnetic dosimetry 1011…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, real-color volume models from real-color sectioned images (> 24 bits color) are naturally superior to grayscale volume models (< 16 bits gray),1213 since the sectioned images are superior to MRIs 141516. One reason why only gray color volume models can be produced is because the software can read only digital imaging and communications in medicine (DICOM) format, which includes information of a patient, scanning methods, etc 8917…”
Section: Introductionmentioning
confidence: 99%